Os imigrantes palestinos na América Latina - Jardim, Denise Fagundes (Estudos Avançados, 2006)
QUANTIFYING Palestinian immigration and appraising their course in Latin America are topics shaping themselves as a research challenge. In this article, I assess these difficulties and deal with aspects that reveal the Palestinian experience in vis-à-vis continuity with other effluxes of immigrants of Arabian ascent. However, I both suggest that singularities exist and proffer new research possibilities.